2020
DOI: 10.1055/a-0990-9114
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transhepatic biliary drainage may be the preferred preoperative drainage method in hilar cholangiocarcinoma

Abstract: Background and study aims Preoperative biliary drainage of hilar cholangiocarcinoma (HC) is controversial. The goal of this study was to compare the clinical outcome and associated complications for types II, III, and IV HC managed by percutaneous transhepatic biliary drainage (PTBD) and endoscopic retrograde cholangiopancreatography (ERCP). Patients and methods Between January 2011 and June 2017, a total of 180 patients with II, III, and IV HC were enrolled in this retrospective cohort study. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
1
12
0
3
Order By: Relevance
“…In terms of procedure-related complications ( e.g. , cholangitis and pancreatitis) two other studies found PTBD to be superior to ERCP[ 63 , 64 ]. Another critical aspect is the cost associated with each method.…”
Section: Endoscopic Vs Percutaneous Biliary Drainage — Pro and Consmentioning
confidence: 99%
“…In terms of procedure-related complications ( e.g. , cholangitis and pancreatitis) two other studies found PTBD to be superior to ERCP[ 63 , 64 ]. Another critical aspect is the cost associated with each method.…”
Section: Endoscopic Vs Percutaneous Biliary Drainage — Pro and Consmentioning
confidence: 99%
“…Most of the studies report the incidence of post-intervention cholangitis in the setting of malignant biliary obstruction. In the study by Saluja et al, 43% of the GBC patients had cholangitis at baseline evaluation, requiring biliary drainage [5]. The grade of cholangitis was not reported.…”
Section: Discussionmentioning
confidence: 96%
“…Biliary drainage represents an important palliation strategy for these patients [4]. In general, endoscopic drainage is the preferred choice for malignant lower end biliary obstruction [5]. In patients with GBC with perihilar involvement, percutaneous transhepatic biliary drainage (PTBD) is better than endoscopic drainage [6].…”
Section: Introductionmentioning
confidence: 99%
“…The authors described a cut-off value of 2.5 mg/dL and 6.2 mg/dL for morbidity and mortality, respectively [32]. In the case of major hepatic resection, biliary drainage of the FLR should be strongly recommended [33,34]. There are two biliary drainage procedures: percutaneous transhepatic biliary drainage (PTBD) and endoscopic biliary drainage (EBD).…”
Section: Biliary Drainage and Future Liver Remnant Quantification Before Lrmentioning
confidence: 99%